True first-pass effect in basilar artery occlusions: First-pass complete reperfusion improves clinical outcome in stroke thrombectomy patients. (July 2021) - Abdullayev, N.; Maus, V.; Behme, D.; Barnikol, U.B.; Kutschke, S.; Stockero, A.; Goertz, L.; Celik, E.; Zaeske, C.; Borggrefe, J.; Schlamann, M; Liebig, T.; et al.
Highlights: Single pass complete reperfusion in acute basilar artery occlusion is an independent predictor of favorable outcome. Multiple passes with complete reperfusion might impair favorable patient recovery. The choice of endovascular techniques should therefore focus on a successful first pass with a complete reperfusion. Abstract: Background: Complete reperfusion (mTICI 3) in anterior circulation ischemic stroke patients after a single mechanical thrombectomy (MT) pass has been identified as a predictor of favorable outcome (modified Rankin Score 0–2) and defined as true first-pass effect recently. This effect has not yet been demonstrated in posterior circulation ischemic stroke. We hypothesized a true first-pass effect for the subgroup of acute basilar artery occlusions (BAO). Methods: Consecutive patients with acute thromboembolic occlusions in the posterior circulation, treated between 2010 and 2017, were screened and all BAO patients with complete angiographic reperfusion and known symptom onset included for unmatched and matched analysis after adjustment for multiple confounding factors (demographics, time intervals, stroke severity, posterior circulation Alberta Stroke Program early computed tomography Score and comorbidity. The primary objective was outcome at 90 days between matched cohorts of single pass vs. multi pass complete reperfusion patients. Results: 90 MTs in BAO were analyzed, yielding 56 patients with known symptom onset, in whom we achieved complete reperfusion (mTICI 3), depending on whether complete reperfusion was achieved after a single pass (n = 28) or multiple passes (n = 28). Multivariable analysis of 56 non-matched patients revealed a significant association between first-pass complete reperfusion and favorable outcome (p < 0.01). In matched cohorts (n = 7 vs. n = 7), favorable outcome was only seen if complete reperfusion was achieved after a single pass (86% vs. 0%). Conclusion: Single pass complete reperfusion in acute basilar artery occlusion is an independent predictor of favorable outcome. Achieving complete reperfusion after multiple passes might impair favorable patient recovery.